2016
DOI: 10.1161/circep.115.003818
|View full text |Cite
|
Sign up to set email alerts
|

Inverted U-Shaped Relation Between the Risk of Sudden Cardiac Death and Maximal Left Ventricular Wall Thickness in Hypertrophic Cardiomyopathy

Abstract: H ypertrophic cardiomyopathy (HCM) is an inherited myocardial disorder characterized by increased left ventricular wall thickness, which is not solely explained by abnormal loading conditions. 1 The clinical perception is that the more severe the hypertrophy, the higher is the risk of sudden cardiac death (SCD) 2 and left ventricular maximal wall thickness (MWT) is one of several clinical features used to guide prophylactic implantable cardioverter defibrillator (ICD) therapy. [1][2][3] However, patients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…This finding is in keeping with recent reports from other independent pediatric populations, which have described a nonlinear association between interventricular septal thickness and left ventricular posterior wall thickness Z scores and SCD risk, plateauing at a Z score of 20 using the Boston normative data. 18,29,30 It is also in keeping with the results of a large adult HCM study (n=3673) 20 and suggests that the relationship between LVH and MLVWT is similar in adult and pediatric patients. The mechanism underlying these observations is unknown, but possible explanations include competing causes of death in those with severe LVH or alternative molecular arrhythmogenic pathways in those with milder hypertrophy.…”
Section: Lvh and Risk Prediction In Childhood Hcmsupporting
confidence: 80%
“…This finding is in keeping with recent reports from other independent pediatric populations, which have described a nonlinear association between interventricular septal thickness and left ventricular posterior wall thickness Z scores and SCD risk, plateauing at a Z score of 20 using the Boston normative data. 18,29,30 It is also in keeping with the results of a large adult HCM study (n=3673) 20 and suggests that the relationship between LVH and MLVWT is similar in adult and pediatric patients. The mechanism underlying these observations is unknown, but possible explanations include competing causes of death in those with severe LVH or alternative molecular arrhythmogenic pathways in those with milder hypertrophy.…”
Section: Lvh and Risk Prediction In Childhood Hcmsupporting
confidence: 80%
“…This study follows the findings of an inverted U-shaped relationship between the risk of SCD and MLVWT in adults (≥16 years) by O’Mahony et al 6 The inverted U-shape of this relation implies that the estimated risk of SCD increases with worsening hypertrophy to reach plateau and declines thereafter. O’Mahony et al 6 had shown that in adult patients, the cumulative incidence of SCD risk increased with 5 mm increments in MLVWT, but beyond MLVWT ≥35 mm the risk of SCD was not greater than the baseline HCM group with MLVWT≤14 mm. Similarly, Norrish et al 5 have shown that estimated risk of SCD at 5 years peaked at an MLVWT Z score of +23; beyond which no further increase in risk was seen, and instead, there was a fall in the estimated risk of SCD.…”
supporting
confidence: 90%
“…Maximal WT has long been considered a key aspect of SCD risk stratification and is included in all stratification scores 1 15 30 40. Different studies reported an increased risk of SCD in patients with a maximal WT of ≥30 mm, although few data are available with extreme LVH (≥35 mm)41 and a paradoxical reduction in SCD risk has been reported recently in individuals with LVH ≥35 mm 42…”
Section: Scd Stratificationmentioning
confidence: 99%